2008
DOI: 10.1113/jphysiol.2007.147652
|View full text |Cite
|
Sign up to set email alerts
|

Functional contributions of synaptically localized NR2B subunits of the NMDA receptor to synaptic transmission and long‐term potentiation in the adult mouse CNS

Abstract: The NMDA-type glutamate receptor is a heteromeric complex composed of the NR1 and at least one of the NR2 subunits. Switching from the NR2B to the NR2A subunit is thought to underlie functional alteration of the NMDA receptor during synaptic maturation, and it is generally believed that it results in preferential localization of NR2A subunits on the synaptic site and that of NR2B subunits on the extracellular site in the mature brain. It has also been proposed that activation of the NR2A and NR2B subunits resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 58 publications
8
53
0
Order By: Relevance
“…GluN2A-and GluN2B-containing NMDARs differ in channel kinetics, open probability, ligand affinity, and the interaction with intracellular signaling and scaffold proteins (14). Previous studies have demonstrated that GluN2A and GluN2B are expressed predominantly at the synapse and extrasynaptic locations, respectively (12,13,45,46). Functionally, GluN2A-containing NMDARs mediated roughly 68% of the synaptic current and 27% of the extrasynaptic current.…”
Section: Discussionmentioning
confidence: 99%
“…GluN2A-and GluN2B-containing NMDARs differ in channel kinetics, open probability, ligand affinity, and the interaction with intracellular signaling and scaffold proteins (14). Previous studies have demonstrated that GluN2A and GluN2B are expressed predominantly at the synapse and extrasynaptic locations, respectively (12,13,45,46). Functionally, GluN2A-containing NMDARs mediated roughly 68% of the synaptic current and 27% of the extrasynaptic current.…”
Section: Discussionmentioning
confidence: 99%
“…7 A, C) under physiological [Mg 2ϩ ] o conditions (0.8 mM). Furthermore, the portion of NR2B-containing NMDAR current is ϳ40% in the lateral amygdala, 20% in hippocampus (Miwa et al, 2008), and ϳ15% in the PFC synapses (Zhao et al, 2005). Electron microscopy studies show that NMDARs at synapses in the lateral amygdala contain larger number of NR2B subunits than synapses in the hippocampal CA1 (Miwa et al, 2008).…”
Section: Regional Specificity Of Mgtmentioning
confidence: 99%
“…Furthermore, the portion of NR2B-containing NMDAR current is ϳ40% in the lateral amygdala, 20% in hippocampus (Miwa et al, 2008), and ϳ15% in the PFC synapses (Zhao et al, 2005). Electron microscopy studies show that NMDARs at synapses in the lateral amygdala contain larger number of NR2B subunits than synapses in the hippocampal CA1 (Miwa et al, 2008). Since the degree of LTP is strongly correlated with the size of the synaptic NMDA current, the above data might also explain why the LTP magnitude in the lateral amygdala synapses is higher than that in the IL-PFC under control conditions (Figs.…”
Section: Regional Specificity Of Mgtmentioning
confidence: 99%
See 1 more Smart Citation
“…NR2B is an important positive regulator of learning and memory by promoting synaptic plasticity and LTP 16, 17. The balance between positive and negative learning and memory‐regulating genes and proteins is key to the formation, maintenance, as well as retrieval of memory.…”
Section: Introductionmentioning
confidence: 99%